ANALISA PENINGKATAN KAPASITAS JALAN AMPERA KOTA PONTIANAK UNTUK PERGERAKAN LALU LINTAS TAHUN 2025 - Petamis, Adnan Gilang; AS, Syafaruddin; Kadarini, S. Nurlaily (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
Growth and development of the city is what brings the impact of problems on the traffic system. Where the increasing number of vehicles passing that is not comparable with the infrastructure and facilities that have been available. St. Ampera stretches along 2.9 km with a width of 6 meters road is one of the main roads located in the city of Pontianak. St. Ampera is categorized as the Secondary Arterial Road Network and is included in the upgrading of the inner ring road network in Pontianak. The government is building a new line of St. Ampera which is under construction. Although it is hampered by social problems, the government will continue to gradually build up 400 to 500 meters of roads annually and promise to complete the new route in an undetermined time. Therefore, this condition causes the need for performance analysis and how big the role of the new path in distributing traffic flow to St. Ampera based on the degree of saturation and speed of traffic flow at present (year 2015) up to 10 (ten) years to be coming (year 2025).In analyzing the effect of road capacity change, it is necessary to have traffic data in the form of traffic volume, side barrier and road geometry before and after the new road is constructed so that it can be seen and compared how big the influence of the new road to the performance on St. Ampera. And the need for an overview of changes in vehicle volume so it can be known how much influence the increase in road capacity to the degree of saturation and speed.Based on the comparison data can be seen in 2015 from traffic pattern survey results in 2015, seen peak hour flow for segment A occurred at 11:00 to 12:00 pm by 666 smp / hour and for segment B occurred at 17:00 to 18:00 WIB of 808 smp / hour. From the comparison of degree of saturation based on vehicle volume change in 2015 can be seen that St. Ampera is said to be not jammed that is the degree of saturation <0.85 that is with degree of saturation of 0.293 in segment A and 0.329 in segment B. For the projection in 2025 can be seen that to the degree saturation in all segments is> 0.85, this illustrates that in 2025 the level of service at St. Ampera is already very bad, level E ie traffic volume close to capacity, unstable current, speed sometimes stalled. For comparison of degree of saturation of projection result 2025 (2/2 UD) with change of road capacity (4/2 D) it can be seen there is decrease 59,33% for segment A and 59,31% for segment B. Based on the increase can be seen service level changes, by 2025 the projected service level is E turns to B where the current is stable, the speed begins to be limited by traffic conditions, the driver has enough freedom to choose speed.Keywords: Capacity Building, Congestion, Performance, Service Level